Molecular characterization of carnivore protoparvovirus 1 circulating in domestic carnivores in Egypt - Ndiana, Linda A.; Lanave, Gianvito; Zarea, Aya A. K.; Desario, Costantina; Odigie, Eugene A.; Ehab, Fouad A.; Capozza, Paolo; Greco, Grazia; Buonavoglia, Canio; Decaro, Nicola (Frontiers in Veterinary Science, 2022)
Canine parvovirus (CPV) and feline panleukopenia virus (FPV), now included in the unique species Carnivore protoparvovirus 1 (CPPV), have been circulating in dogs and cats for several decades, and are considered the causes of clinically important diseases, especially in young animals. While genetic evidence of the circulation of parvoviruses in Egyptian domestic carnivores exists since 2016, to date, all available data are based on partial fragments of the VP2 gene. This study reports the molecular characterization of CPPV strains from Egypt based on the full VP2 gene. Overall, 196 blood samples were collected from dogs and cats presented at veterinary clinics for routine medical assessment in 2019 in Egypt. DNA extracts were screened and characterized by real-time PCR. Positive samples were amplified by conventional PCR and then sequenced. Nucleotide and amino acid changes in the sequences were investigated and phylogeny was inferred. CPPV DNA was detected in 18/96 dogs (18.8%) and 7/100 cats (7%). Phylogenetic analyses based on the full VP2 gene revealed that 9 sequenced strains clustered with different CPV clades (5 with 2c, 2 with 2a, 1 with 2b and 1 with 2) and 1 strain with FPV clade. All three CPV variants were detected in dog and cat populations with a predominance of CPV-2c strains (7/18, 38.9%) in dog samples, thus mirroring the circulation of this variant in African, European and Asian countries. Deduced amino acid sequences alignment revealed the presence of previously unreported unique mutations S542L, H543Q, Q549H and N557T in the Egyptian CPV-2c strains.